Penerapan Metode Reorder Point (ROP) dalam Persediaan Sabun Cuci Merk “B-Light” pada UD. Dhofir Jaya di Desa Pemecutan Kaja Kecamatan Denpasar Utara - Mahwan Mahwan (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to determine (1) the level of demand for washing soap brand "B-Light" at UD. Dhofir Jaya in 2019 (2) Calculation of ordering for washing soap brand "B-Light" using the Reorder Point (ROP) method at UD. Dhofir Jaya in 2019 (3) The level of demand for washing soap with the "B-Light" brand after the Reorder Point (ROP) method was applied in ordering the "B-Light" brand of washing soap at UD. Dhofir Jaya. The type of this research is descriptive. The subject of this research is Mr. Ahmad Dhofir, as company owner. The Object of this research is determining right time to reorder by UD. Dhofir Jaya with Reorder Point (ROP) method. The data needed of this research are data on the purchase of goods, the purchase price and the selling price, the average demand per day, the duration of delivery of goods is calculated from the day of order, and determining the safety stock. The method to collecting data of this research is interview and observation method. Data analysis of this research is using descriptive analysis technique . the results of this research is, (1) average demand of the mounth is 2.515 box, (2) reorder made when Inventory in warehouse is 284 box and (3) the demand incresed to 873 box after using ROP method.